Applying the AcciMap methodology to investigate the tragic Sewol Ferry accident in South Korea. (March 2017) - Lee, Samuel; Moh, Young Bo; Tabibzadeh, Maryam; Meshkati, Najmedin
Abstract: This study applies the AcciMap methodology, which was originally proposed by Professor Jens Rasmussen (1997), to the analysis of the tragic Sewol Ferry accident in South Korea on April 16, 2014, which killed 304 mostly young people and is considered as a national disaster in that country. This graphical representation, by incorporating associated socio-technical factors into an integrated framework, provides a big-picture to illustrate the context in which an accident occurred as well as the interactions between different levels of the studied system that resulted in that event. In general, analysis of past accidents within the stated framework can define the patterns of hazards within an industrial sector. Such analysis can lead to the definition of preconditions for safe operations, which is a main focus of proactive risk management systems. In the case of the Sewol Ferry accident, a lot of the blame has been placed on the Sewol's captain and its crewmembers. However, according to this study, which relied on analyzing all available sources published in English and Korean, the disaster is the result of a series of lapses and disregards for safety across different levels of government and regulatory bodies, Chonghaejin Company, and the Sewol's crewmembers. The primary layers of the AcciMap framework, which include the political environment and non-proactive governmental body; inadequate regulations and their lax oversight and enforcement; poor safety culture; inconsideration of human factors issues; and lack of and/or outdated standard operating and emergency procedures were not only limited to the maritime industry in South Korea, and the Sewol Ferry accident, but they could also subject any safety-sensitive industry anywhere in the world. Highlights: Sewol Ferry accident that killed 304 people was a national disaster in South Korea. AcciMap methodology identified root-causes (and their interactions) of the Sewol accident. The behavior of front-line operators was conditioned by the influence of the higher-up AcciMap layers. Lack of strong and independent safety oversight regime was a notable contributor to this accident.